Adaptive evolution of a generalist parasitoid: implications for the effectiveness of biological control agents. (5th August 2013) - Zepeda‐Paulo, Francisca A.; Ortiz‐Martínez, Sebastián A.; Figueroa, Christian C.; Lavandero, Blas
Abstract The use of alternative hosts imposes divergent selection pressures on parasitoid populations. In response to selective pressures, these populations may follow different evolutionary trajectories. Divergent natural selection could promote local host adaptation in populations, translating into direct benefits for biological control, thereby increasing their effectiveness on the target host. Alternatively, adaptive phenotypic plasticity could be favored over local adaptation in temporal and spatially heterogeneous environments. We investigated the existence of local host adaptation in Aphidius ervi, an important biological control agent, by examining different traits related to infectivity (preference) and virulence (a proxy of parasitoid fitness) on different aphid‐host species. The results showed significant differences in parasitoid infectivity on their natal host compared with the non‐natal hosts. However, parasitoids showed a similar high fitness on both natal and non‐natal hosts, thus supporting a lack of host adaptation in these introduced parasitoid populations. Our results highlight the role of phenotypic plasticity in fitness‐related traits of parasitoids, enabling them to maximize fitness on alternative hosts. This could be used to increase the effectiveness of biological control. In addition, A. ervi females showed significant differences in infectivity and virulence across the tested host range, thus suggesting a possible host phylogeny effect for those traits.